Copper-catalyzed asymmetric allylic C–H amination of alkenes using N-arylhydroxylamines. Issue 13 (20th May 2021) - Murru, Siva; Mokar, Bhanudas D.; Bista, Ramesh; Harakat, Dominique; Le Bras, Jean; Fronczek, Frank; Nicholas, Kenneth M.; Srivastava, Radhey S.
Abstract : The first Cu-catalyzed asymmetric allylic C–H amination of alkenes with N -aryl hydroxylamines has been developed. Metal-complexes isolation, ESI-MS analysis and the DFT calculations provided key insights on mechanistic pathway. Abstract : The first copper-catalyzed asymmetric allylic C–H amination of alkenes using N -arylhydroxylamines as aminating agents is disclosed. Enantioselective C–N bond formation reactions are promoted in the presence of Cu(MeCN)4 PF6 as a pre-catalyst and R -(+)-BINAM as a chiral ligand. This protocol delivers chiral N -aryl allylamines in good yields and enantioselectivities. Data regarding the effect of ligand structure and solvents on the efficiency and enantioselectivity of amination reactions are presented. Furthermore, isolation of the metal–ligand–nitroso complex, ESI-MS reaction monitoring analysis and computational calculations provided additional insights into the mechanistic pathway. DFT modeling of the reaction pathway suggests that the stereoselectivity is determined in the conversion of (BINAM)Cu(PhNO)(η 2 -alkene) + to (BINAM)Cu( N -aryl allylhydroxylamine) via a concerted, asynchronous transition state for C–N bond formation. This catalytic approach features operational simplicity, high product yields with good enantioselectivity, and no byproducts except for water.